2021
DOI: 10.3390/cryst11020181
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Polymers in Dicyanamido-Cadmium(II) with Diverse Network Dimensionalities

Abstract: The synthesis and structural characterization of six dicyanamido-cadmium(II) complexes are reported: catena-[Cd(μ1,3-dca)(μ1,5-dca)(3-ampy)] (1), catena-[Cd3(μ1,3,5-dca)2(μ1,5-dca)4(pyNO)2(H2O)2] (2), catena-{Cd(H2O)2(μ1,5-dca)2](2,6-lut-NO)} (3), catena-[Cd(Me2en)(μ1,5-dca)2] (4), catena-[Cd(Me4en)(μ1,5-dca)2] (5), and [Cd(1,8-damnp)2(dca)2] (6), where dca = dicyanamide anion, 3-ampy = 3-aminopyridine, pyNO = pyridine-N-oxide, 2,6-lut-NO = 2,6-lutidine-N-oxide, Me2en = N,N-dimethyl-ethylenediamine, Me4en = N,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The complexes' molar conductance indicated that all complexes except Sm(III) were electrolytes. The conductance value of Co(II), Ni(II), and Zn(II) chelates revealed 1:2 and of Cu(II) complex revealed 1:1 24 …”
Section: Results and Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…The complexes' molar conductance indicated that all complexes except Sm(III) were electrolytes. The conductance value of Co(II), Ni(II), and Zn(II) chelates revealed 1:2 and of Cu(II) complex revealed 1:1 24 …”
Section: Results and Analysismentioning
confidence: 96%
“…The conductance value of Co(II), Ni(II), and Zn(II) chelates revealed 1:2 and of Cu(II) complex revealed 1:1. 24 T A B L E 1 Physicochemical data for the (H 4 L) ligand and its metal chelates.…”
Section: Analytical Datamentioning
confidence: 99%
“…The dca ligands exhibit two different bonding modes, μ-1,5- and μ-1,3,5-bridging, creating a 3D network structure. 22 The μ-1,5- and μ-1,3,5-bridging dca anions form 2D planes, which are further connected by μ-1,5-bridging anions, resulting in interlaced 3D networks (Fig. 2b).…”
Section: Resultsmentioning
confidence: 99%
“…21 The networks formed by of small pseudo halides (N 3 − , NCS − and NCO − ) and the longer dicyandiamide, dca (dca = N(CN) 2 − ), with divalent metal( ii ) are considered to be the most studied pseudo halide compound networks. 22 Our group successfully synthesized [Et 3 ( n -Pr)P][Cd(dca) 3 ], [Et 3 P(CH 2 ) 2 Cl][Cd(dca) 3 ], and [Et 3 P(CH2) 2 F][Cd(dca) 3 ] ferroelastic compounds using the cation templates of anionic metal-dca (M-dca) networks. 23–25 These compounds all employ each metal( ii ) atom coordinated to the six terminal N atoms of the dca ligand, forming a distorted octahedral geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Complexes with 2-,3-or 4-NH2py ligands show that NH2py tends to act as a monodentate ligand by binding to the central atom via the N pyridine ring. Complexes that have been reported such as [Ni(NCS)2(2-NH2py)2.C4H10O] [7], {∞[Cd(µ-SCN)2(4-NH2py)2]} [8], [Cu(SCN)2(x-NH2py)2] (x=2,3, or 4) [4], and [M(3-NH2py)2(dca)2] (M=Mn2+, Cu2+,Cd2+, or Co2+; dca = dicyanamide) [1,[9][10][11], [AgL(x-NH2py)2] [12][13][14][15][16] demonstrated the formation of polymer complexes via bridge formation by bidentate ligands such as dicyanamide, thiocyanate and azide. Several other complexes with monodentate ligands such as Cl¬ such as…”
Section: Introductionmentioning
confidence: 99%